In vitro assay and inhibition of 9-cis-epoxycarotenoid dioxygenase (NCED) from Solanum lycopersicum and Zea mays - Harrison, Peter J.; Chandler, Jake; Thompson, Andrew J.; Bugg, Timothy D. H. (Elsevier, 2024)
The article reports methods for the expression and assay of 9-cis-epoxycarotenoid cleavage dioxygenase (NCED), an enzyme involved in the biosynthesis of phytohormone abscisic acid in plants. A method for the preparation of the unstable substrate 9′-cis-neoxanthin from fresh spinach is described. The inhibition of Solanum lycopersicum NCED by a series of aryl hydroxamic acid inhibitors is illustrated, and inhibitors D2 and D4 are assayed against NCED isozymes from Zea mays.